Desain Portable Hanger Penjemur Pakaian Untuk Manula - Salsabila, Kamila (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2022)
Abstract — The more people get older, the more health complaints they feel in their activities, such as on tiptoe, which is caused by a type of arthritis, namely gout. The pain is usually felt in the joints, such as the big toe and elbow. One of the activities of the elderly in the household that can be disturbed by the disease is drying clothes. With a clothesline area that is narrow, then the hanging technique can be used to minimize the use of too much area. In the process of hanging clothes for drying, elderlies are required to stand on tiptoe and stretch out their arms to reach the height of the clothesline repeatedly. This study was designed to provide facilities so that elderlies with a narrow clothesline can dry their clothes without having to stand on tiptoe and stretch out their arms many times. The method used in the implementation of this research begins with field observations, interviews, identification of activities carried out during drying clothes, so as to find the design solutions needed for the problems of the elderly in drying. The results obtained are a portable clothesline hanger design that can be raised and lowered according to needs that are in accordance with ergonomic principles. Abstrak — Semakin bertambahnya usia, semakin banyak keluhan kesehatan yang dirasakan dalam beraktivitas, seperti dalam menjinjitkan kaki yang dikarenakan oleh jenis radang sendi (arthritis) yaitu asam urat. Rasa sakit yang dirasakan biasanya terdapat pada bagian persendian, seperti jempol kaki dan siku. Aktivitas manula dalam rumah tangga yang dapat terganggu oleh penyakit tersebut salah satunya adalah menjemur pakaian. Dengan area jemuran yang sempit, maka teknik menggantung dapat digunakan untuk meminimalisir penggunaan area yang terlalu banyak. Dalam proses menggantungkan pakaian untuk dijemur, manula diharuskan untuk menjinjit dan melentangkan tangan agar mencapai tinggi tali jemuran secara berulang-ulang. Penelitian ini dibuat untuk menyediakan fasilitas agar manula dengan area jemuran yang sempit dapat menjemur pakaian tanpa harus menjinjit dan melentangkan tangan berkali-kali. Metode yang dilakukan dalam pelaksanaan penelitian ini diawali dengan observasi lapangan, wawancara, identifikasi aktivitas yang dilakukan selama menjemur pakaian, sehingga menemukan solusi desain yang diperlukan untuk permasalahan manula dalam menjemur. Hasil yang diperoleh adalah desain hanger jemuran pakaian portable yang dapat dinaik turunkan sesuai kebutuhan yang telah sesuai dengan prinsip ergonomi.